Answer :
Answer:
LAST OPTION: [tex](6-\sqrt{21},6+\sqrt{21})[/tex]
Step-by-step explanation:
1. Subtract [tex]12x[/tex] from both sides of the equation:
[tex]x^2-12x= 12x- 15-12x\\\\x^2-12x=-15[/tex]
2. Since [tex]b=12[/tex]:
[tex](\frac{b}{2})^2=(\frac{12}{2})^2=(6)^2[/tex]
3. Now can complete the square. Add [tex](6)^2[/tex] to both sides of the equation:
[tex]x^2-12x+6^2=-15+6^2[/tex]
4. Simplifying:
[tex](x-6)^2=21[/tex]
5. Solve for "x":
[tex]\sqrt{(x-6)^2}=\±\sqrt{21}\\\\x-6=\±\sqrt{21}\\\\x=6\±\sqrt{21}\\\\x_1=6+\sqrt{21}\\\\x_2=6-\sqrt{21}[/tex]
6. The solution set is:
[tex](6-\sqrt{21},6+\sqrt{21})[/tex]